Asymptotic expansions of probability distributions - Bikelis, Algimantas; Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2009)
Asymtotic expansionsfor the probabilitydistributionsof sums of independentrandom variables are studied in this paper.
Keywords: series of independent random variables; compound Poisson distribution; Bergström–Grigelionis’ asymtotic expansions